Aquaporin-4 serostatus does not predict response to immunotherapy in neuromyelitis optica spectrum disorders. (November 2018) - Mealy, Maureen A; Kim, Su-Hyun; Schmidt, Felix; López, Reydmar; Jimenez Arango, Jorge A; Paul, Friedemann; Wingerchuk, Dean M; Greenberg, Benjamin M; Kim, Ho Jin; Levy, Michael
Background: Debate exists about whether neuromyelitis optica spectrum disorder seronegative disease represents the same immune-mediated attack on astrocytic aquaporin-4 as in seropositive disease. Objective: We investigated whether response to common treatments for neuromyelitis optica spectrum disorder differed by serostatus, as assessed by change in annualized relapse rate. Methods: We performed a multicenter retrospective analysis of 245 patients with neuromyelitis optica spectrum disorder who were treated with either rituximab or mycophenolate mofetil as their first-line immunosuppressive treatment for disease prevention. Patients were followed for a minimum of 6 months following treatment initiation. Results: In those started on rituximab, the pre-treatment annualized relapse rates for seropositive and seronegative patients were 1.81 and 1.93, respectively. On-treatment annualized relapse rates significantly declined to 0.32 (seropositive; p  < 0.0001) and 0.12 (seronegative; p  = 0.0001). In those started on mycophenolate mofetil, the pre-treatment annualized relapse rates for seropositive and seronegative patients were 1.79 and 1.45, respectively. On-treatment annualized relapse rates declined to 0.29 (seropositive; p  < 0.0001) and 0.30 (seronegative; p  < 0.005). Conclusion: In this international collaboration involving a large number of neuromyelitis optica spectrum disorder patients, treatment was effective regardless of serostatus. This suggests that treatment should not differ when considering these treatments.